Efficacy of mobile-based educational intervention using Instructional Systems Design in promoting preventive behaviors for sexually transmitted infections among Iranian women: a randomized controlled trial - Afsaneh Karami Juyani; Fatemeh Zarei; Raziyeh Maasoumi (BMC, 2024)
Abstract Background Women who are sexually active are at risk of sexually transmitted infections (STIs), which can cause serious difficulties for their reproductive health. However, despite the high global burden of STIs, most infections are preventable with education for behavioral change. The purpose of this study is to investigate the Efficacy of Mobile-Based Educational Intervention Using Instructional Systems Design in Promoting Preventive Behaviors for Sexually Transmitted Infections among Iranian Women. Methods This randomized controlled trial aimed at promoting preventive behaviors related to STIs in Iranian women with an educational intervention based on the Instructional Systems Design (ISD) in 2022. The participants in this study were recruited from a single center, specifically the Health House No. 3 located in District 11 of Tehran Municipality. Two instruments were used in the present study: a) a valid scale titled: "Four-Scale of STI Preventive Behaviors", and b) a researcher-made Questionnaire titled: "Social perception affecting sexually transmitted infections (SOPESTI)". These tools contain 8 demographic items and specific questions with a total of 68 five-point Likert scales. The intervention comprised three phases: a pre-test (baseline), a training program, and two follow-up assessments (4 and 12 weeks after the start of the training program). The experimental group received education through a mobile app, while the control group received no intervention. SPSS v.26 was used, with a significance level of P < 0.05. The chi-square test, Fisher's exact test, independent t-tests, analysis of covariance (ANCOVA), and repeated measures ANOVA were used to analyze the data. Results A total of 80 women, with a mean age of 36.524 ± 6.91 (experiment group) and 34.78 ± 8.20 (control group), respectively, participated in the trial. The study revealed a statistically significant difference in the mean score for eight domains, including STIs Knowledge, STIs Vulnerability, STIs Preventive Self-efficacy, STIs Prevention intentions, STIs Perceived social exclusion, STIs Perceived cognitive barriers, STIs Perceived social support, and STIs Perceived risks in the experiment group following the intervention compared to before the intervention (p < 0.05). Conclusion The results of this study showed that a mobile-based educational intervention based on the ISD model had a significant effect on the preventive behaviors of STIs in Iranian women. These results highlight the potential benefit of mobile health in enhancing reproductive health. Trial registration ClinicalTrials.gov IRCT20200602047638N1. Registered on 22 May 2021 with the IRCTID, V1.0. https://www.irct.ir/trial/55632